PENGARUH MIND MAPPING TERHADAP MOTIVASI BELAJAR SISWA KELAS VIII DI SMP NEGERI 12 TARAKAN - Safitri, Anggun Dwi; Rahmi, Siti (Jurnal Bimbingan dan Konseling Borneo, 2019)
The purpose of this study was to determine the effect of mind mapping on the learning motivation of class VIII of Junior High School 12 Tarakan in the academic year 2018/2019. This study uses a quantitative approach type quasi experimental design in the form of nonequivalent control group design. The population of this study is 191 eighth grade students of Junior High School 12 Tarakan. The research sample consisted of 20 students divided into the experimental group and the control group. Data collection method uses the AMS (Academic Motivation Scale) scale with a Likert scale. This study uses the relliabel formula to test the validity of the AMS (Academic Motivation Scale) scale with the results of 49 statement items there are 24 valid items. The data analysis technique in this study is descriptive statistical analysis and inferential analysis hypothesis testing using the SPSS 24.0 for Windows program mann whitney u.Based on the results of statistical data analysis results of the calculation of the mann whitney u using SPSS 24.0 for windows obtained a significance value = 0.000 <? = 0.05. This shows the significance value of less than 0.05 can be concluded that the hypothesis is accepted, which means that there is an influence of mind mapping on the learning motivation of VIII graders in Tarakan 12 Middle School in 201/2019 Academic Year.  Keywords: Mind Mapping, Learning Motivation